Ultra-Processed Food (UPF) Consumption and The Risk of Mental Health Problems among Adolescents: A Narrative Review - Amelia, Fhadilla (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Mental health problems are increasing among adolescents. One modifiable risk factor is diet, particularly the consumption of ultra-processed foods (UPF), which is notably high in this age group. Objective: This narrative review aims to summarize recent scientific evidence on the association between UPF consumption and the risk of mental health problems in adolescents. Methods: A literature search was conducted using two major databases (Google Scholar and PubMed) with the keywords (“ultra-processed food” OR “UPF”) AND (“adolescents” OR “teenagers” OR “youth”) AND (“depression” OR “anxiety” OR “mental health issues”). After a selection process involving title, abstract, and full-text screening, 11 articles were included in the narrative analysis, which involved identifying patterns, similarities, differences, and links between UPF consumption and adolescent mental health outcomes. Results: Most studies showed that high UPF consumption is associated with an increased risk of mental health issues among adolescents, including depression, anxiety, anxiety-induced sleep disturbance, internalizing and externalizing symptoms, and reduced quality of life. Some studies reported varying results based on gender, assessment tools, and population characteristics. Conclusion: High consumption of UPF may be a potential risk factor for mental health problems in adolescents. Nutrition education and policies limiting UPF intake should be considered as part of preventive and promotive strategies for adolescent mental health. Further longitudinal and interventional studies are needed to strengthen causal evidence and evaluate the effectiveness of preventive efforts.